The latest global burden of liver cancer: A past and present threat - Oh, Joo Hyun; Jun, Dae Won (Clinical and molecular hepatology, 2023)
[6] performed a comparative analysis focusing on age-adjusted DALYs and mortality rates, but crude numbers were rarely presented. [...]it is still difficult to answer the question of how to distribute goods, and further economic evaluations are needed. [...]primary liver cancer has always posed a significant threat to global health, both in the past and in the future. [...]they also suggested a social agenda for the social burden of alcohol-related liver cancer, which has a relatively low social interest.